Pelestarian Warisan Budaya melalui Tradisi Petik Laut: Analisis Interaksi Simbolik terhadap Kearifan Lokal Masyarakat Lekok - Syafa Ayunda Putri; Nurma Yuwita (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
The Sea Picking Tradition is a cultural ritual of the coastal community in Jatirejo Village, Lekok District, Pasuruan Regency, which is held annually as a form of gratitude for marine products. Amidst the current of modernization, this tradition has an important meaning in preserving local wisdom and cultural heritage of coastal communities. This study aims to understand the symbolic meaning contained in the series of Sea Picking Tradition processions and examine its role as a form of local wisdom in maintaining community identity and solidarity. Cultural symbols displayed through offerings, decorated boats, traditional clothing, collective prayers, and other socio-cultural activities are seen as having deep meanings that represent the relationship between humans with nature, each other, and the Creator. The research method used is a qualitative approach with descriptive methods and symbolic interaction analysis. Data were obtained through observation, interviews, and documentation, then analyzed to uncover the hidden meanings in cultural symbols. The results show that the symbols in the Sea Picking Tradition form collective meanings that strengthen individual self-concept, social relations, and ecological awareness of coastal communities. This tradition serves as a means of strengthening social solidarity, solidifying local cultural identity, and preserving spiritual values ​​and local wisdom amidst the challenges of modernization. Thus, the Petik Laut tradition serves not only as a ritual of gratitude but also as a cultural heritage that must be preserved to maintain the social, cultural, and spiritual values ​​of coastal communities.